2005
DOI: 10.2320/matertrans.46.2015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fabrication Method on Microstructure and Properties of Al<SUB>2</SUB>O<SUB>3</SUB>&ndash;TiC Composites

Abstract: Al 2 O 3 -TiC composite powders were prepared by high-energy ball milling (HEBM) and wet-planetary ball milling (WPBM) from different starting materials, and subsequently sintered by Spark Plasma Sintering (SPS). The effect of the fabrication method on the microstructure and properties of Al 2 O 3 -TiC composites was investigated. The results showed that Al 2 O 3 -TiC composites with fine and homogeneous microstructures were prepared by SPS from high-energy ball milled reactants, which had excellent comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Researchers have studied the percolation threshold and conductive properties of new advanced ceramics with respect to the proportion of conductive additives [52, 53]. The first studies on samples of composites and nanocomposites of Al 2 O 3 +TiC system produced by spark plasma sintering (SPS) were reported by the group headed by Prof. Zhang [54, 55, 56]. Then, a research group under the supervision of Prof. Torrecillas and Prof. Moya proposed an advanced SPS method assisted by electrical current to produce new nanocomposites of Al 2 O 3 +SiC w +TiC.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have studied the percolation threshold and conductive properties of new advanced ceramics with respect to the proportion of conductive additives [52, 53]. The first studies on samples of composites and nanocomposites of Al 2 O 3 +TiC system produced by spark plasma sintering (SPS) were reported by the group headed by Prof. Zhang [54, 55, 56]. Then, a research group under the supervision of Prof. Torrecillas and Prof. Moya proposed an advanced SPS method assisted by electrical current to produce new nanocomposites of Al 2 O 3 +SiC w +TiC.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work on TiC composites demonstrated Al 2 O 3 -TiC bulk composites by spark plasma sintering (SPS) had much improved mechanical and electrical conduction properties simultaneously [21]. Compared to particles, carbon nanotubes (CNTs) and carbon fibers (C f ) [22] are better to bear the load and prevent crack propagation in matrix for their large aspect ratios.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of a chemical reaction between Al 2 O 3 and TiC, which leads to the generation of gas, contributes to the high densification of each sample. In situ reaction synthesis is advantageous for obtaining a fine and uniform distribution of the second phase that contributes to densification 24 . Fabrication via in situ reaction of Ti and CNTs yields ATCT composites with a high relative density of nearly 100%.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that in situ reaction synthesis produces composites with more homogeneous microstructures (than those resulting from conventional methods) even from coarse starting powders 22,23 . Zhang et al 24 prepared Al 2 O 3 ‐TiC composites via in situ reaction of Ti (~40 μm) and graphite (~40 μm) and a final TiC size of 200 nm was realized. Lee et al 25 reported that Al 2 O 3 ‐TiC composites with a TiC size of ~2 μm were obtained through in situ reaction synthesis using TiO 2 (<0.5 μm) and graphite (5‐10 μm).…”
Section: Introductionmentioning
confidence: 99%